Children’s preferences among six novel moxifloxacin and linezolid-dispersible tablet formulations - G. Hoddinott; H.R. Draper; N. Vanqa; S. Myeni; S. Staples; T. Sachs; M. Raffique; N. Tshethu; M. Palmer; L. Viljoen; K. Inabathina; R. Taneja; et al. (IJTLD Open)
BACKGROUND: Moxifloxacin (MFX) and linezolid (LZD) are key components of rifampicin-resistant TB treatment regimens. Currently, available dispersible tablet formulations of both drugs have poor palatability in children. We evaluated children’s preferences for more child-friendly formulations from two generic manufacturers. METHODS: This was a randomised, cross-sectional ‘swish-and-spit’ taste panel study at two sites in South Africa. Each manufacturer created three flavour-blend variants for each drug. Healthy child volunteers 5–17 years old were sampled stratified by age, sex, and ethnic group and completed a preference rank-ordering and five acceptability 5-point Likert scales. We explored the blends’ acceptability using summary, comparative, and ranking statistics. RESULTS: Ninety-seven and 96 children contributed data for the MFX and LZD drug blends, respectively. For both manufacturers’ MFX blends, the Friedman test showed children had a statistically significant preference for novel options over the Existing blend (Q(2) = 24,937; P < 0.001, and Q(2) = 21.213; P < 0.001, respectively). Even the most preferred MFX blend had sub-optimal acceptability, especially for one manufacturer. Children did not have a clear preference for both manufacturers’ LZD blends. These findings were not influenced by age, sex, or ethnic group. CONCLUSION: Children across a broad age spectrum can provide meaningful input on the palatability preferences of TB drug formulations. Novel MFX formulation blends were recommended for development, but acceptability remains suboptimal.